2021
DOI: 10.3390/computers10090118
|View full text |Cite
|
Sign up to set email alerts
|

360°-Based Virtual Field Trips to Waterworks in Higher Education

Abstract: 360° models are a form of virtual reality (VR) that allow the viewer to view and explore a photorealistic object from multiple locations within the model. Hence, 360° models are an option to perform virtual field trips (VFT) independent of time and location. Thanks to recent technical progress, 360° models are creatable with little effort. Due to their characteristics of visualization and explorability, 360° models appear as excellent learning tools, especially when additional didactic features, such as annota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
2
3
0
Order By: Relevance
“…The quick accessibility makes it possible to use the virtual tour flexibly in teaching as well as for homework and theses. These findings are in line with previous studies by Demir ( 2014 ), Cliffe ( 2017 ), Stainfield et al ( 2000 ), Pugsley et al, 2022 , Evelpidou et al ( 2021 ) and Wolf et al ( 2021 ), who found that VR platforms, as a supplement to field trips or field courses, provide access independent of time and space. This generally allows students to work autonomously and interactively.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The quick accessibility makes it possible to use the virtual tour flexibly in teaching as well as for homework and theses. These findings are in line with previous studies by Demir ( 2014 ), Cliffe ( 2017 ), Stainfield et al ( 2000 ), Pugsley et al, 2022 , Evelpidou et al ( 2021 ) and Wolf et al ( 2021 ), who found that VR platforms, as a supplement to field trips or field courses, provide access independent of time and space. This generally allows students to work autonomously and interactively.…”
Section: Discussionsupporting
confidence: 92%
“…However, all users agreed that for cases where a real excursion is not possible and as a basic supplement to regular classes, the virtual excursion is an excellent tool. This result falls in line with findings of Stainfield et al ( 2000 ), Kingston et al ( 2012 ), Pugsley et al ( 2022 ), Evelpidou et al ( 2021 ) and Wolf et al ( 2021 ) that state that VFT can always be seen as an addition to real field trips rather than a replacement. Overall, positive feedback from students clearly prevailed.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations